2021
DOI: 10.3389/fphar.2021.669403
|View full text |Cite
|
Sign up to set email alerts
|

AGR3 Regulates Airway Epithelial Junctions in Patients with Frequent Exacerbations of COPD

Abstract: Background: The mechanisms underlying differences in the susceptibility to chronic obstructive pulmonary disease (COPD) exacerbations between patients are not well understood. Recent studies have shown that the patients with frequent COPD exacerbations is related to specific protein expression in lung tissue. Anterior gradient 3 (AGR3) is expressed in airway epithelial cells in the lung and proteomic analysis revealed that its expression is decreased in patients with frequent COPD exacerbations. Moreover, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…A higher amount of occludin was found for the non-COPD patients compared to the COPD patients (see representative samples: Figure 1a). the present results corroborated an immunohistochemistry (IHC) study that assessed that the expression level of occludin was significantly decreased in COPD patients [55]. Next, we compared the expression levels of occludin in the lung tissue samples of the never-smokers and smokers.…”
Section: Occludin Expression Is Decreased In Lung Tissue Of Smokerssupporting
confidence: 84%
“…A higher amount of occludin was found for the non-COPD patients compared to the COPD patients (see representative samples: Figure 1a). the present results corroborated an immunohistochemistry (IHC) study that assessed that the expression level of occludin was significantly decreased in COPD patients [55]. Next, we compared the expression levels of occludin in the lung tissue samples of the never-smokers and smokers.…”
Section: Occludin Expression Is Decreased In Lung Tissue Of Smokerssupporting
confidence: 84%
“… 89 A recent study in human lung tissues showed that E‐cadherin, occludin and zonula occludens‐1 (ZO‐1) expression were lower in the frequently exacerbated COPD patients than in the infrequently exacerbated COPD group. 90 Overall, these results suggest a mechanism in COVID‐19 severity namely increased systemic inflammation due to the continuous epithelial barrier disruption.…”
Section: The Final Factor: the Immune Responsementioning
confidence: 82%
“…Comorbid chronic obstructive pulmonary disease (COPD) was identified as a risk factor for mortality in COVID‐19 patients admitted in ICU with an HR of 1.68 (95% CI: 1.28–2.19) in multivariate analysis in Lombardy, Italy 89 . A recent study in human lung tissues showed that E‐cadherin, occludin and zonula occludens‐1 (ZO‐1) expression were lower in the frequently exacerbated COPD patients than in the infrequently exacerbated COPD group 90 . Overall, these results suggest a mechanism in COVID‐19 severity namely increased systemic inflammation due to the continuous epithelial barrier disruption.…”
Section: The Final Factor: the Immune Responsementioning
confidence: 99%
“…E-cadherin is an adhesion molecule responsible for the organization of interepithelial junctions [72,73]. Numerous studies have shown that E-cadherin was markedly decreased in smokers and COPD [68,[74][75][76][77][78]. Particularly, the expression of E-cadherin was positively related to FEV1/VC ratio [74].…”
Section: Alterations Of Epithelial-mesenchymal Transformation Biomark...mentioning
confidence: 99%